Changement climatique et viticulture en Champagne : du constat actuel aux prévisions du modèle ARPEGE-Climat sur l’évolution des températures pour le XXIe siècle - Gérard Beltrando; Elodie Briche (EchoGéo)
In Champagne vineyard, Climate Change already observed since the end of 1980’s, showed by precocity of phenology as harvests and quality improvement of grapes. This temporal evolution calls out to wine growers because if this evolution continues, it could become harmful to grape production quality (summer heat waves, lack of water, high alcohol rate…). In the aim to find responses concerning temperature evolution (means and daily extremes) in a context of  greenhouse concentration rise, daily temperature data calculated by ARPEGE-Climate model (Météo-France) are validated by comparison to Reims-Courcy station on period control from 1950 to 2000. Secondly, future simulations from 2001 to 2100 are discussed under the IPCC emission scenarios [B1 (optimistic) A1B (moderate) and A2 (pessimistic)]. Results show non linear trend with an air temperature warming but also significant temperature variability according to scenario. Temperature simulations of 2060’s could provoke severe damages on vineyard activity, particularly for A2 scenario.